2022
DOI: 10.1186/s13052-022-01211-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on lifestyle behaviors in children and adolescents: an international overview

Abstract: The adverse effects of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) are not limited to the related infectious disease. In children and adolescents, serious risks due to the coronavirus disease 2019 (COVID-19) pandemic are also related to its indirect effects. These include an unbalanced diet with an increased risk of weight excess or nutritional deficiencies, increased sedentary lifestyle, lack of schooling, social isolation, and impaired mental health.Pediatricians should be aware of the side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 146 publications
1
50
0
3
Order By: Relevance
“…In fact, vaccination guarantees psychological and social well-being, through the resumption of usual sociocultural activities, that were suspended during the pandemic. This suspension had some psychological repercussions, especially in the young population ( 42 , 43 ). Vaccination also provides physical well-being, reducing hospital admissions and serious manifestations of infection.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, vaccination guarantees psychological and social well-being, through the resumption of usual sociocultural activities, that were suspended during the pandemic. This suspension had some psychological repercussions, especially in the young population ( 42 , 43 ). Vaccination also provides physical well-being, reducing hospital admissions and serious manifestations of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Limited and restricted outdoor activities have been correlated with the decline in cardiorespiratory health and increased cases of both underweight and overweight in children. The term 'Covibesity' refers to the increased obesity rates during the lockdown period due to poor eating habits, and an unbalanced diet (Scapaticci et al, 2022).…”
Section:  Lifestyle and Behavioursmentioning
confidence: 99%
“…Pre-existing sleep problems and feelings of anxiety, sadness, and loneliness further increase the vulnerability to psychological distress and stressors during the pandemic(Kiss et al, 2022). Sleep disturbance due to increased screen time among children had majorly impacted emotional health, immune response, and risk of cardio-metabolic diseases(Scapaticci et al, 2022). It was also reported that…”
mentioning
confidence: 99%
“…However, the COVID-19 statistics related to children are increasingly seen to be underestimations. 3 , 4 Unavoidable factors were behind this. At the beginning of the pandemic the scarce human and material resources were focused on top priority adults—senior citizens, adults with comorbidities, pregnant women, healthcare workers, etc.…”
mentioning
confidence: 99%
“…Within the research fraternity, however, the role of children in the transmission of SARS-CoV-2 remained contentious. 3 Early in the epidemic a systemic meta-analysis by Zhu et al, 6 included 43 studies from 12 countries comprising 611 individuals including 102 children in 213 SARS-CoV-2 transmission clusters. Only eight (3.8%) of these clusters yielded pediatric index cases, suggesting that children’s role in the transmission of COVID-19 was limited.…”
mentioning
confidence: 99%